Exploring the interaction of knee and ankle component use on mobility test performance in people with unilateral transfemoral amputation. Issue 6 (16th December 2021) - Barnett, Cleveland T.; Hughes, Liam D.; Sullivan, Amy E.; Strutzenberger, Gerda; Levick, Jodie L.; Bisele, Maria; De Asha, Alan R.
Abstract : Background: Ankle-foot and knee components are important determinants of mobility for individuals with transfemoral amputation. Individually, advanced ankle-foot and knee components have been shown to benefit mobility in this group of people. However, it is not clear what effect a variety of combinations of ankle-foot and knee components have on mobility test performance. Objectives: To assess whether outcomes from mobility tests in people with unilateral transfemoral amputation are influenced by varying combinations of ankle-foot and knee components. Study Designs: Repeated measures. Methods: Nine adults with unilateral transfemoral amputation completed the two-minute walk test, the timed up-and-go test, the L-test, and a custom locomotion course in four randomized prosthetic conditions. These conditions were each a combination of an ankle-foot component (rigid, nonarticulating [RIG] or hydraulically articulating [HYD]) and a knee component (non–microprocessor-controlled [NMPK] or microprocessor-controlled [MPK]). The test-retest reliability and concurrent validity of the custom locomotion course were also established. Results: The best performance in all mobility tests was associated with the MPK + HYD combination, followed by the MPK + RIG, NMPK + HYD, and NMPK + RIG combinations. This effect was statistically significant for the two-minute walk test ( P = 0.01, η p 2 = 0.36) and on threshold for the L-test ( P = 0.05, η p 2 = 0.36), but not statistically significant for the locomotion course ( P = 0.07, η p 2 = 0.38) or the timed up-and-go test ( P = 0.12, η p 2 = 0.22). Locomotion course performance had good to excellent test-retest reliability and strong concurrent validity. Conclusion: Using a combination of a HYD ankle-foot and a MPK knee resulted in the highest performance in mobility tests. This was observed in contrast to combinations of prosthetic components that included a rigid ankle-foot component and/or a NMPK knee component.